Attitude Change of Hearing Health Professionals on Bone-Anchored Hearing Devices Over Time in a Developing Country - Necdet Ardıç, Fazıl; Demir, Emine; Aydemir, Gökçe; Terlemez, Şengül (ENT Updates, 2024)
Background: Bone-anchored hearing instruments (BAHIs) are an important alternative solution for hearing loss in a particular group of patients. This study aims to examine shifts in attitudes about BAHIs among hearing health professionals over time. Methods: A survey was designed to assess the knowledge and attitude of otorhinol aryngologists (ENT) and audiologists (Au) concerning BAHIs. The survey was administered in 2019 and 2023 at various conferences. Results: The survey received 243 responses (122 in 2019 and 121 in 2023). Among these, 186 (77%) were from ENTs, while 49 (20%) were from Aus. Notably, the preference for using BAHI for conductive and mixed hearing loss cases increased from 19.3% to 47.9%. The number of individuals with prior experience decreased, yet those who applied BAHIs grew. Signifcant shifts were observed in patient selection based on hearing level, hearing loss type, and clinical condition. The profession and experience emerged as infuential factors in these changes. Conclusion: While most subjects recognized the signifcance of hearing rehabilitation, their fundamental knowledge and familiarity with BAHIs remained limited. A broader implementation of educational and training initiatives focusing on BAHIs is essential to enhance understanding and profciency in this area.